Sound Symbolism in Indonesian and English - Dharmawati Dharmawati; Mulyadi Mulyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study conducted on sound symbolism in Indonesian and English. The objective of this study is to map the sound symbolism in Indonesian and English in accordance with the typology of sound symbolism.  This study is qualitative descriptive method by using the theory of natural semantic metalanguage pioneered by Wierzbicka (1996). The data was taken from text books and newspaper. The research stage in analyzing the data was carried out in some steps, namely data collection, data classifying, and data presenting. The result showed that from four types of sound simbolism, there are two types which have similar pattern both Indonesian and English, they are in coporeal sound symbolism and imitative sound symbolism.